(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article investigates the translation of metaphors whose meaning is bound up with national mentality, on the material of English and Uzbek. Starting from the cognitive premise that metaphor is a mechanism of thought rather than an ornament of speech, the study asks what happens to a metaphor when it must cross between two typologically and culturally distant languages. Metaphorical units were collected from Betty Smith’s “A Tree Grows in Brooklyn” and Utkir Hoshimov’s “Dunyoning ishlari”, reconstructed at the conceptual level, and examined for their lexico-stylistic features and their behaviour under translation. Four translation outcomes are identified — direct transfer, conceptual transfer with substituted realisation, dual (literal-plus-interpretive) rendering, and compensation or explanation — and each is linked to the degree of overlap between the two mentalities. The article argues that translation adequacy for such metaphors depends less on lexical correspondence than on whether the receiving mentality supplies the association the source metaphor presupposes, and it draws practical conclusions for translator training and bilingual lexicography.